2021
DOI: 10.1021/acsanm.0c02747
|View full text |Cite
|
Sign up to set email alerts
|

Irregularly Shaped Mn2O3 Nanostructures with High Surface Area for Water Oxidation

Abstract: Water oxidation is an energy-consuming, four-electron-transfer reaction and is essential for solar fuel production from water. Catalysts based on precious metals such as RuO2 and IrO2 show high efficiency for oxygen evolution reaction. However, these catalysts are less abundant and expensive. To date, earth-abundant water oxidation catalysts still exhibit less activity for water oxidation. Herein, we report the synthesis of high surface area Mn2O3 nanomaterials for an efficient photocatalytic water oxidation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…The FT-IR spectra of AT-CMO-60 (3-MnO 2 ) having two distinctive vibrational bands at 363 and 500 cm À1 arising from the bending and stretching vibrations of the Mn-O bond of MnO 6 octahedra of the 3-MnO 2 phase. 39,42,43 With increasing the heating temperature of the AT-CMO-60 sample, shoulder vibrational bands started appearing and become clear till 400 C. The shoulder bands developed at 325, 550, and 650 cm À1 represent the characteristic Mn-O vibrational modes in the MnO 6 octahedral co-ordination of b-MnO 2 . [44][45][46] At 400 C a pure phase of b-MnO 2 formed.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The FT-IR spectra of AT-CMO-60 (3-MnO 2 ) having two distinctive vibrational bands at 363 and 500 cm À1 arising from the bending and stretching vibrations of the Mn-O bond of MnO 6 octahedra of the 3-MnO 2 phase. 39,42,43 With increasing the heating temperature of the AT-CMO-60 sample, shoulder vibrational bands started appearing and become clear till 400 C. The shoulder bands developed at 325, 550, and 650 cm À1 represent the characteristic Mn-O vibrational modes in the MnO 6 octahedral co-ordination of b-MnO 2 . [44][45][46] At 400 C a pure phase of b-MnO 2 formed.…”
Section: Resultsmentioning
confidence: 98%
“…On further increasing the heating temperature to 450 C, the vibrational spectrum matches with the Mn 2 O 3 phase. 39,47,48 Though, the XRD pattern of AT-CMO-450 shows that the major part of the sample is b-MnO 2 with a small amount of Mn 2 O 3 , the FT-IR spectrum shows that the major part of the sample consists of Mn 2 O 3 with a small Hence, it can be concluded that a major part of the sample is Mn 2 O 3 with a small amount of b-MnO 2 , which is further conrmed by the X-ray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It involves two reaction steps: a hydrogen evolution reaction (HER) and an oxygen evolution reaction (OER). [5][6][7] However, an anodic oxygen evolution reaction involves the transfer of four electrons, 8 and the reaction kinetics is very slow. Due to the inevitable overpotential generated by the two electrodes, the cell voltage of electrolytic water far exceeds the theoretical voltage of 1.23 V, which is unfavorable for energy saving hydrogen production.…”
Section: Introductionmentioning
confidence: 99%